Hubungan Geographical Inquiry dengan Kemampuan Berpikir Kritis, Prestasi Belajar dan Self-Efficacy - Mohammad Amin Lasaiba (Universitas Indraprasta PGRI Jakarta, 2023)
The inquiry learning process can train students to develop knowledge, skills, and practices. The problem in inquiry-based learning lies in the challenges of developing the knowledge, skills, and practices required by students. This research aims to examine the effectiveness of geographical inquiry in terms of critical thinking skills, learning achievement, and self-efficacy. This study employed a quasi-experimental design with a population of tenth-grade students at MAN 1 Ambon City, with the research conduction was in March 2023. The sample class was selected using purposive sampling with instruments consisting of tests and questionnaires analysed using the independent t-test. The research results indicate that the significance value of the t-test for critical thinking skills, learning achievement, and geography students' self-efficacy is less than 0.05, thus rejecting the null hypothesis (Ho). Therefore, the Geographical Inquiry learning method is effective for use in school-based learning.